Morphological and Molecular Diversity of the Neglected Genus Rhizomastix Alexeieff, 1911 (Amoebozoa: Archamoebae) with Description of Five New Species - Zadrobílková, Eliška; Smejkalová, Pavla; Walker, Giselle; Čepička, Ivan (The Journal of eukaryotic microbiology, 2016)
The genus Rhizomastix is a poorly known group of amoeboid heterotrophic flagellates living as intestinal commensals of insects, amphibians or reptiles, and as inhabitants of organic freshwater sediments. Eleven Rhizomastix species have been described so far, but DNA sequences from only a single species have been published. Recently, phylogenetic analyses confirmed a previous hypothesis that the genus belongs to the Archamoebae; however, its exact position therein remains unclear. In this study we cultured nine strains of Rhizomastix, both endobiotic and free-living. According to their light-microscopic morphology and SSU rRNA and actin gene analyses, the strains represent five species, of which four are newly described here: R. bicoronata sp. nov., R. elongata sp. nov., R. vacuolata sp. nov. and R. varia sp. nov. In addition, R. tipulae sp. nov., living in the intestine of crane flies, is separated from the type species, R. gracilis. We also examined the ultrastructure of R. elongata sp. nov., which revealed that it is more complicated than the previously described R. libera. Our data show that either the endobiotic lifestyle of some Rhizomastix species has arisen independently from other endobiotic archamoebae, or the free-living members of this genus represent a secondary switch from the endobiotic lifestyle.
Keywords: Base Sequence; geologické sedimenty; Genes, rRNA; druhová specificita; Species Specificity; Fresh Water; Phylogeny; ultrastructure; DNA, Protozoan; aktiny; Actins; sladká voda; protozoální DNA; morphology; Archamoebae; sekvence nukleotidů; Sequence Analysis, DNA; phylogeny; Geologic Sediments; geny rRNA; sekvenční analýza DNA; Amoebozoa; mikroskopie; fylogeneze; Microscopy